The Video-Based Pastoral Counselling on the Spiritual Recovery of Generation Alpha at Rumah Belajar Baba - Jhonnedy Kolang Nauli; Hizkia Lumban Tungkup; Saragih, Eka Widia; Jonidius Illu (Department of Guidance and Counseling, FIP, Undiksha, 2025)
This paper explores the impact of video-based pastoral counselling on the spiritual recovery of Generation Alpha. As digital technology becomes increasingly woven into our daily lives, understanding its role in fostering spiritual growth and recovery among younger generations is more important than ever. Recent research shows that video-based pastoral counselling tends to attract higher-income participants, with 61% belonging to upper-class demographics and 39% from lower-income backgrounds. To evaluate the effectiveness of this intervention, we collected data through structured surveys that assessed participants' spiritual well-being both before and after the counselling sessions. A chi-squared analysis was performed to examine the normality of the data distribution, resulting in a calculated value of 0. 654. This figure falls below the critical value of 3. 841 at a 5% significance level with five degrees of freedom, indicating that the data adheres to a normal distribution. Consequently, we retain the null hypothesis (H₀) and reject the alternative hypothesis (H₁). This study asserts that video-based pastoral counselling serves as an effective means of promoting spiritual recovery among Generation Alpha. Furthermore, it provides valuable insights into how digital tools can be integrated into pastoral care and offers practical recommendations for incorporating technology into spiritual development initiatives.